Smoking, behavioral factors and familial environment: a population based study with brazilian adolescents (2013)
Objective The present study was aimed at assessing the association between smoking and both behavioral and environmental factors among adolescents in the public school system in the city of Campina Grande (north-eastern Brazil).Methods An analytical cross-sectional study was carried out involving 574 schoolchildren aged 10 to 19 years old; it involved using a structured questionnaire addressing behavioral and environmental factors and smoking. The Chi-squared test and Fisher’s exact test were used for the statistical analysis (5 % level of significance).Results Smoking prevalence was 3.3 %. The lowest age regarding tobacco use for the first time was eight years old and the 11 to 14 year old age group had the greatest frequency of initiation into this habit (44.3 %); 84.3 % of tobacco users smoked between one and 10 cigarettes per day. Smoking was associated with delays in schooling (p=0.047), gender (p=0.016), alcohol use and frequency of alcohol use (p and lt;0.001) and the relationship with one’s father (p=0.014) and mother (p=0.004).Conclusions Despite the low prevalence, an early initiation into smoking was found, suggesting that educational campaigns should be directed towards younger age groups. Alcohol use stood out amongst the variables studied, suggesting that smoking is influenced by both its use and the intensity of consumption.